The Study of Key Stratum Location and Characteristics on the Mining of Extremely Thick Coal Seam under Goaf - Gaochuan Guo; Yongkang Yang (Advances in Civil Engineering)
The basis of traditional ground pressure and strata control techniques is the key strata theory, wherein the position of the key stratum can easily be determined for coal seams with regular thickness and without goaf. However, in the case of mining ultrathick coal seams underneath goaf, the traditional methods used for the calculation of key stratum position need to be improved in order to account for the additional coal seam thickness and the presence of an upper goaf. This study analyzed the failure height and collapse characteristics of overlying strata during excavation for determining the structure of the failed overlying strata. The results indicate that the intercalation and overlying strata gradually evolve into a large “arch structure” and a small “arch structure” during longwall mining, respectively. A mechanical model of the bearing characteristics of the interlayer key strata structure was established according to the structure of the intercalation rock layer, which is a hinged block structure. The results of the model indicate that the maximum principal stress occurs when the key strata portion of the arch structure bears the overlying load. Consequently, the movement and position of the interlayer key strata can be evaluated throughout the mining process of the ultrathick coal seams underneath goaf. This method was used to determine the position of interlayer key stratum of overlying strata in Xiegou coal mine. And the results agree with that of the engineering practice. The results are significant to determine the key strata position during ultrathick coal seam underneath goaf longwall mining.